Tahlīlu Qīmah al-Insāniyyah fī Mawādi Kitābi Taʿlīmi al-Lugah al-ʾArabiyyah li aṣ-Ṣaffi aṡ-Ṡāminu fī al-Marḥalah al-Mutawasiṭah as-Sanah 2020: Analysis of Humanistic Values in the Teaching Materials of Arabic Textbook for Eighth-Grade MTs in 2020 - Arpin Aminuddin Hrp; Khuntum Khaira Ummah; Aisyah Petricia; Abul Ma’ali; Ahmad Nawirul Huda (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
The presence of humanistic values in educational materials has a significant positive impact on improving students' self-quality because humanistic values are one of the main objectives of learning. The objectives of this research are to identify humanistic values in Arabic language teaching materials in the middle stage for the eighth grade in 2020. The approach used in this research is qualitative with desk study. The data collection method in this research is observation and document analysis. The steps of data analysis in this research include data identification, analysis process, and conclusion. The results of this research contain Arabic language teaching materials in the middle stage for the eighth grade in 2020 with humanistic values such as (1) Responsibility, for example, present in Figure 1: Exercises, and Figure 2: Reading Lesson. (2) Sociability, present in Figure 3: Dialogue between two students. (3) Literature and ethics, present in Figure 4: Expressions of gratitude and apology. (4) Cooperation, present in Figure 5: Reading Lesson, and Figure 6: Exercises on converting nominal sentences to verbal sentences. (5) Creativity and innovation, present in Figure 7: Grammar Lesson. (6) Discipline, in Figure 8: Dialogue between two students. Keywords: Arabic, Educational Materials, Humanistic Values, Teaching Book ملخص إن وجود القيمة الإنسانية في المواد التعليمية له تأثير إيجابي كبير على تحسين الجودة الذاتية لدى الطلاب، لأن القيمة الإنسانية هي أحد الأهداف الرئيسية في التعلم. أما أهداف هذا البحث فهو لمعرفة القيمة الإنسانية في مواد كتاب تعليم اللغة العربية في المرحلة المتوسطة للصف الثامن السنة 2020. المدخل المستخدم في هذا البحث هو  المدخل النوعي بالدراسة المكتبية. أما طريقة جمع البيانات في هذا البحث هي ملاحظة والوثائق. وأما خطوات تحليل البيانات في هذا البحث، فهي تحديد البيانات وعملية التحليل والخلاصة. أما نتائج هذا البحث فهي تحتوي مواد كتاب التعليم اللغة العربية في المرحلة المتوسطة للصف الثامن السنة 2020 على قيمة إنسانية منها: (1) المسؤولية، على سبيل المثال موجودة في الصورة 1: التدريبات، والصورة 2: درس القراءة. (2) العشائرية، موجودة في الصورة 3: الحوار بين طالبين. (3) الأدب والأخلاق، موجودة في الصورة 4: عبارات الشكر والاعتذار. (4) المعاونة، موجودة في الصورة 5: درس القراءة، موجودة في الصورة 6: التدريبات على تحويل الجملة الاسمية إلى جملة فعلية. (5) الإبداع والابتكار، موجودة في الصورة 7: درس القواعد،  (6) الانضباط، في الصورة 8: الحوار بين طالبين. الكلمات المفتاحية: القيمة الإنسانية، مواد التعليمية، كتاب التعليم، اللغة العربية